Wetting films: A technique for probing the microscopic meniscus using white light interferometry - Fung, C.; Sedev, Rossen; Connor, J. (Elsevier, 2014)
The affinity between a liquid and a solid is characterised by the contact angle. Traditional contact angle measurement techniques such as the sessile drop and Wilhelmy plate methods provide macroscopic information about the solid-liquid-vapour contact line. Our knowledge of the microscopic details is incomplete due to experimental limitations. In order to examine a liquid meniscus on a microscopic scale we adapted the white light interferometry used in the Surface Force Apparatus. With this approach we extract film thickness with nanometre resolution and its variation over tens of micrometres along the solid surface. We describe here the technique and its application to the spreading of an aqueous 0.1 M KCl droplet on a freshly cleaved sheet of mica. The film profile was also followed throughout the spreading and subsequent evaporation of an ethanol droplet. Microscopic details obtainable with this technique can provide a check for theoretical descriptions of wetting. They could offer a unique insight into the early stages of coating, liquid creeping and surface reactivity. Such details are relevant to corrosive films creeping on pipes in process plants, evaporation from heat exchangers, and the application and drying of paints and adhesives.